Inventarisasi Jenis Pohon di Kawasan Pusat Pembinaan, Pendidikan, dan Pelatihan (Pusbindiklat) Peneliti - LIPI untuk Menunjang Faktor Keselamatan - DAMAYANTO, I PUTU GEDE P.; NARAKUSUMO, RADEN PRAMESA; KINTAMANI, ENDANG; PUTRI, ADE LIA; ROSYIDAH, A’LIYATUR; OCTAVIANA, SENLIE; BUDIARTO, BUGI RATNO; POHAN, FIQOLBI NURO; PUTRIE, RAHAYU FITRIANI WANGSA; RACHMADIYANTO, ARIEF NOOR (Jurnal Arsitektur Lansekap; Vol.3, No.2, Oktober 2017DO - 10.24843/JAL.2017.v03.i02.p03, 2017)
The area within Pusbindiklat Peneliti-LIPI (The National Training and Education Center for Researchers Development-Indonesian Institute of Sciences) has been planted with many trees as an effort for reforestration and increasing aesthetic value. Unfortunately, the management of Pusbindiklat Peneliti-LIPI paid less attention to the trees potency and its characteristic as well as inventorizing all trees. This study aim to inventorize tree species based on their morphological characteristic in order to know the potency concerned with safety. Research was conducted through inventorizing and scoring the suitability factors of all trees, determining the tree plantation points, which is converted to the map of Pusbindiklat Peneliti-LIPI. In addition, direct interviews were also conducted to the civitas of Pusbindiklat Peneliti-LIPI. Trees that have been found in the area of Pusbindiklat Peneliti-LIPI consist of 20 family, 42 species, and 217 individuals. From the inventory of the trees, there were 11 species which were unsuitable with the criteria of urban forest vegetation parameter. Moreover, based on the map of trees species at Pusbindiklat Peneliti-LIPI area, there are 85 individual from 20 species of trees that are not suitable to be planted in Pusbindiklat Peneliti, since they were planted near the parapet wall and buildings of Pusbindiklat Peneliti-LIPI.